2017
DOI: 10.18291/njwls.v7i1.81400
|View full text |Cite
|
Sign up to set email alerts
|

Economic Evaluation of Supported-Employment Inspired Program for Pupils With Intellectual Disabilities

Abstract: <div class="page" title="Page 1"><div class="layoutArea"><div class="column">In this study, we investigate whether, or to what degree, a ‘business case’ could be made for implementation of a Supported-Employment (SE) inspired program for pupils with intellectual disabilities (IDs), starting during the final school years. For this aim, we do a quasi-experimental before-after intervention impact evaluation of such a project funded by the European Social Fund in the Swedish city of Örebro (135,0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Twelve studies that scored 70% or more on quality focused on IPS, were linked to RCTs, and concluded that it was cost-effective [17,18,20,25,30,31,[33][34][35][36][41][42][43]. Only two IPS studies were from the USA [30,36]; most IPS [3,18,20,23,31,41,51,56], where IPS services have been implemented and there is good access to welfare and health registry data to follow-up service users.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Twelve studies that scored 70% or more on quality focused on IPS, were linked to RCTs, and concluded that it was cost-effective [17,18,20,25,30,31,[33][34][35][36][41][42][43]. Only two IPS studies were from the USA [30,36]; most IPS [3,18,20,23,31,41,51,56], where IPS services have been implemented and there is good access to welfare and health registry data to follow-up service users.…”
Section: Discussionmentioning
confidence: 99%
“…Five out of seven cost-benefit analyses of SE interventions had positive net benefits [3,47,49,52,56], for instance, $6,627 to $40,012 per participant in Switzerland under different scenarios over 20 years [52]. A US study on SE for autism, intellectual disabilities, and other mental health conditions, from a public purse perspective, had various benefit-to-cost ratios, depending the presence of comorbid conditions (without secondary diagnosis = 1.46 versus with secondary diagnosis = 1.49), with the highest net benefits of 2.2 shown for learning disabilities over 6 years [49].…”
Section: Other Supported Employment Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…A standout feature of Waimea's programme was the fostering of microenterprises. In response to NZ's low employment rate for disabled people (Statistics NZ, 2014), the running a micro-enterprise and enabling self-employment are alternative pathways which international research suggests is a promising direction (Ashley & Graf, 2017;Galle Jr & Lacho, 2009;Reddington & Fitzsimons, 2013;Tholén, Hultkrantz, & Persson, 2017). The participants at Waimea felt employers would be more open to offer work if they could meet the students first.…”
Section: Teachingmentioning
confidence: 99%